2015
DOI: 10.1002/mc.22263
|View full text |Cite
|
Sign up to set email alerts
|

miR‐204 is dysregulated in metastatic prostate cancer in vitro

Abstract: During cancer progression, the genome instability incurred rearrangement could possibly turn some of the tumor suppressor micro-RNAs into pro-oncogenic ones. We aimed to investigate miR-204 in the context of prostate cancer progression using a cell line model of different levels of genome instability (LNCaP, PC3, VCaP and NCI H660), as demonstrated by the availability of ERG fusion. We studied the effect of miR-204 modulation on master transcription factors important for lineage development, cell differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…The consensus sequence for TRA2β-binding (GAA) lies within the miR-204-binding site of BCL-2 3′-UTR, TRA2β antagonizes the effects of miR-204 and upregulates BCL-2 expression [54]. Such a mechanism is very interesting, partially because it can explain why miR-204 regulates expression of its targets with different efficiencies in the way depending on cell lines used [44]. Given that TRA2β mRNA expression is significantly upregulated in colon cancer [54] and prostate cancer tissues compared with paired normal tissues, it is highly possible that TRA2β plays an important role in carcinogenesis by blocking function of miR-204.…”
Section: Factors Regulating Expression and Function Of Mir-204mentioning
confidence: 99%
“…The consensus sequence for TRA2β-binding (GAA) lies within the miR-204-binding site of BCL-2 3′-UTR, TRA2β antagonizes the effects of miR-204 and upregulates BCL-2 expression [54]. Such a mechanism is very interesting, partially because it can explain why miR-204 regulates expression of its targets with different efficiencies in the way depending on cell lines used [44]. Given that TRA2β mRNA expression is significantly upregulated in colon cancer [54] and prostate cancer tissues compared with paired normal tissues, it is highly possible that TRA2β plays an important role in carcinogenesis by blocking function of miR-204.…”
Section: Factors Regulating Expression and Function Of Mir-204mentioning
confidence: 99%
“…Dysregulation of miR-204 is a common feature in a number of cancers, such as breast cancer, acute myeloid leukemia, and prostate cancer (Butrym et al, 2015;Wang et al, 2015;Todorova et al, 2016). Although miR-204 has been found to be downregulated in GC tissues (Zhang et al, 2015a), its expression profile in serum samples and its potential for clinical use are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had extensively confirmed that MicroRNAs played vital roles in tumor metastasis (911). Nevertheless, there are very few comprehensive reports on the prediction and diagnosis values of microRNAs in metastatic PCa (12).…”
Section: Introductionmentioning
confidence: 93%